(untitled) (CIPEEX, 2025)
The aim of this study was to review the main characteristics of cysticercosis. Taenia solium is a flatworm of the Cestoda class with a heteroxenic evolutionary cycle that can cause taeniasis through the ingestion of raw or undercooked pork, causing gastrointestinal symptoms in the small intestine due to parasitism of the hermaphrodite female, that is, the adult worm. Therefore, this parasitosis is known as solitary. In this case, the human being is the definitive host, and the pig, the intermediate host. However, this parasite can also course with the infection of the larval forms in humans, causing cysticercosis. In cysticercosis, contact occurs with another form of Taenia solium, eggs. In this way, the eggs excreted in human feces are ingested, from fecal-oral transmission, that is, through contaminated water and food, and transform into cysticercus larvae that do not lodge in the small intestine, but in different human organs, especially in the central nervous system (CNS), muscle, brain, heart and skin. Symptoms will vary according to the anatomical place where the cysticercus larva is lodged. In the CNS, cysticercosis is called neurocysticercosis and can cause severe neurological symptoms, such as seizures and headaches. The diagnosis can be made using imaging tests, and the differential diagnosis should be made with other pathologies with the appearance of granuloma. If the person does not have taeniasis, the stool test will not be useful, because people with cysticercosis do not eliminate Taenia solium eggs in the stool. Treatment may be promoted with corticosteroids, anticonvulsants, and in some cases, surgery may be necessary. The prevention of cysticercosis includes the ingestion of sanitized water and food, good personal hygiene practices and basic sanitation, among others.